Analysis of the School Literacy Movement with the Utilization of Reading Corner in Elementary School Education Units (Case Study of Grade IV Students at SDN 4 Tambun) - Nasriani (International Journal of Integrative Research, 2023)
This study aims to find out how the school literacy program works, especially in educational units that have implemented the reading corner program. This type of research uses descriptive qualitative research. Data collection techniques used observation of activities in the school literacy program, interviews with school principals, teachers and students as well as documenting activities based on school literacy. Data validation technique uses data source triangulation. Data analysis using data reduction, data display and summary description. The results of this study indicate the implementation of the school literacy movement, especially in fostering students' interest in reading with forms of implementing the school literacy movement including procuring more varied reading material books, carrying out reading activities 15 minutes before learning, optimizing reading corners and creating an environment with a culture of literacy for students learners.